Pengaruh Pemberian Tandan Kosong Sawit dan Kapur Dolomit Sebagai Campuran Media Tanam Terhadap Pertumbuhan Bibit Kelapa Sawit ( Elaeis quenensis Jacq. ) di Main Nursery - Rahmawaty Rahmawaty; Rustam Baraq Noor; Hamidah Hamidah (Universitas Widya Gama Mahakam, 2012)
The Effect of Empty Bunch of Palm and Chalk of Dolomit Giving as Mixture of Plant Media to Growth of Palm Seedling (Elaeis quenensis Jacq) in Main Nursery. Target of research to know the effect of empty bunch of palm and chalk of dolomit giving as mixture of plant media to growth of palm seedling ( elaeis quenensis jacq ) in main nursery. The research was conducted on three months, since March until May 2010 in Palm plantation PT. Rea Kaltim Plantations, Perdana Village, Kembang Janggut District, Kutai Kertanegara Regent. The research was arranged in factorial completely randomized design (Factorial CRD) with factorial experimental design 3 x 3, and 3 replications. The first factor was the empty bunch of palm (T), that consisted 3 levels, they were: (t0) = without the empty bunch of palm/polybag, (t1) = 2kg of the empty bunch of palm/polybag, (t2) = 4kg of the empty bunch of palm/polybag and the second factor was the chalk of dolomit (K), that consisted 3 levels, they were: (k0) = without the chalk of dolomit /polybag, (k1) = 0,2kg of the chalk of dolomit /polybag, (k2) = 0,4kg of the chalk of dolomit /polybag. The result showed that the best result reached by 2kg of the empty bunch of palm/polybag as mixture of plant media to growth of palm seedling ( Elaeis quenensis Jacq ) in main nursery. The chalk of dolomit gave different result, treatment was not significantly influence because not be assisted with activator to quicken the empty bunch of palm dekomposition so that its result can be exploited for the growth of palm seedling. Each factor that was the empty bunch of palm and was the chalk of dolomit given separate factor to growth of palm seedling in main nursery.